(untitled) (REMUNOM, 2025)
This article aims to understand the contributions of Educational Technologies to nursing teaching and training. The guiding research question is: What is the contribution of the use of educational technologies to the professional training of nurses? The study justifies the need for discussion, study, reflection, and development because Educational Technologies are in a consolidation phase in nursing practice and are important for the acquisition and development of competencies and skills. This is a descriptive, integrative review (Zocche et al., 2020). A search for publications in the Virtual Health Library (VHL) resulted in 126 articles in the Medline, BDENF-Nursing, and LILACS databases. Nine articles were selected for review, using the following descriptors separated by the Boolean operator "AND": Nursing, Professional Training, Educational Technologies. The conclusion is that Educational Technologies are relevant for the teaching and learning of future nurses, contributing to a humanized education, promoting inclusion, integrating theory with practice, and strengthening professional nursing training. When used appropriately and combined with active methodologies, they can improve nurses’ education, better equipping them for nursing practice and the job market.